Hierakonpolis Online (2002)
[Dt.:] Auf der Website werden Informationen zur Stadt Hierakonpolis mit (teilweise interaktiven) Grabungsergebnissen, Plänen und eine Bibliographie angeboten. - [Engl.:] On this website information about the city of Hierakonpolis with its (partially interactive) excavation results, plans and a bibliography are offered.